Annual cycle and morphology of lice parasitizing two sympatric African small mammals (Micaelamys namaquensis and Elephantulus myurus) - Lutermann, Heike (University of Pretoria, 2021)
Dissertation (MSc (Entomology))--University of Pretoria, 2021.